(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2021)
This study is based on the quality of wastewater from Hawassa University surroundings, which was assessed to determine its suitability for irrigation purposes during 2019. Grab samples of influent and the treated water were taken for assessing for quality parameters. The study revealed that the treated water could be used for irrigation purpose with some moderate restrictions. Even though Electrical Conductivity (EC) and Total Dissolved Solids (TDS) permit to irrigate fruit trees and fodder crops, there is a risk of soil degradation due to high value of Sodium Adsorption Ratio (SAR). Results also indicated that carbonate, potassium and phosphate exceeded the specified limits for wastewater reuse in agriculture. Despite increased nutritive elements, continuous use of treated sewage water for irrigation will make the soil acidic. Analysis of soil parameters indicated that there is an increase in nitrogen, phosphate and potassium nutrient levels considerably to benefit crop production but increase in soil EC is a serious concern. Int. J. Agril. Res. Innov. Tech. 10(2): 59-65, December 2020